Pengaruh Kompetensi Profesional dan Etos Kerja Guru terhadap Konsep Diri Siswa MTs Swasta - Asni Neli; Saidil Mustar; Hartini Hartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT Based on the facts, almost in junior high school professional competence has not been satisfactory, especially social studies teachers, ironically the attitude of students' self-concept is lower in teaching and learning activities. This fact is determined by many factors, internal factors include lack of interest, weak motivation, weak level of intellectual intelligence, while external factors are teachers influencing student learning outcomes in schools. The weak self-concept of students in the classroom is closely related to the weak professional competence of teachers and the work ethic of teachers. one _ part of the teacher's internal factors which implicitly determine the success of students in growing students' self-concepts, especially in social studies subjects, professional competence and teacher work ethic. Professional teachers are teachers who are able to carry out their duties competently, both conceptually and applicable and have the ability to carry out teacher duties. Research was conducted in private MTs in Rupit District, North Musirawas Regency. The purpose of the study was to determine the effect of teacher professional competence and teacher work ethic on the self-concept of private MTs students in Rupit District, North Musirawas Regency, either simultaneously or partially. The sample in this study were private MTs students in Rupit District as many as 90 students. The results obtained are: The partial test (t test) which was carried out proved the professional competence of teachers and the work ethic of the teacher partially significant effect on the self-concept of private MTs students in Rupit District t count > t table and also significant at 0.001 < 0.05. This means that the variable of professional competence has an effect on students' self-concept. The teacher's work ethic on students' self-concept in private MTs in Rupit District. Where t count > t table and also significant at 0.001 < 0.05. This means that the teacher's work ethic variable has an effect on students' self-concept. Teacher professional competence and teacher work ethic simultaneously significantly influence the self-concept of private MTs students in Rupit District where F count > F table and sig of 0.001 < 0.05. This means that the variables of teacher professional competence and teacher work ethic have an effect on students' self-concept. Keywords : Teacher Professional Competence, Teacher Work Ethic , Student Self Concept